New records of earthworms (Clitellata: Oligochaeta) from Georgia, USA, including eight new state records - Mcgee, Joseph M.; Carrera-Martínez, Roberto; Jr., Mac A. Callaham; Snyder, Bruce A. (Zootaxa, 2024)
We present here new county records for 13 counties within Georgia, USA from the collections of the Georgia Museum of Natural History and the authors. These include four families, eight genera, and 23 species. Of these, eight species are new state records: Amynthas carnosus (Goto & Hatai, 1899); Aporrectodea longa (Ude, 1885); Bimastos parvus (Eisen, 1874); Diplocardia deborahae Damoff & Reynolds, 2017; Diplocardia gatesi Murchie, 1965; Diplocardia michaelseni Eisen, 1899; Metaphire hilgendorfi (Michaelsen, 1892); and Murchieona minuscula (Rosa, 1906). These findings are presented alongside an updated checklist for Middle Georgia building on data compiled by Reynolds (2015) to create a practical record for the region.